Clinical characteristics in subjects with NLRP3 V198M diagnosed at a single UK center and a review of the literature - Rowczenio, Dorota M (BioMed Central, 2013)
INTRODUCTION: Mutations in the NLRP3 gene are associated with the dominantly inherited cryopyrin-associated periodic syndrome (CAPS). The significance of the V198M variant is unclear; it has been reported in association with various CAPS phenotypes and as a variant of uncertain consequence. The aim of this study was to characterize the clinical phenotypes and treatments in individuals with V198M assessed in a single UK center. METHODS: DNA samples from 830 subjects with fever syndromes or a family history of CAPS were screened for mutations in the NLRP3 gene with polymerase chain reaction (PCR) and sequencing. A detailed medical history was available in all cases. Inflammatory disease activity was monitored monthly with measurements of serum amyloid A protein (SAA) and C-reactive protein (CRP) in symptomatic individuals. RESULTS: NLRP3 V198M was identified in 19 subjects. It was found in association with CAPS in five cases, in one patient with Schnitzler syndrome, in three patients who also had a nucleotide alteration in another fever gene, and in three other patients with evidence of an autoinflammatory phenotype. Seven asymptomatic individuals were detected during screening of family members. CONCLUSIONS: The NLRP3 V198M variant shows variable expressivity and reduced penetrance. It may be associated with classical inherited or apparently sporadic CAPS and with atypical autoinflammatory disease of varying severity, intriguingly including Schnitzler syndrome. The factors that influence the pathogenic consequences of this variant remain unknown. However, the remarkable response to interleukin 1 (IL-1) blockade in all but one individual in our series confirms that their clinical features are indeed mediated by IL-1.